Memory for Emotional Pictures in Patients with Alzheimer's Dementia: Comparing Picture-Location Binding and Subsequent Recognition - Marloes J. Huijbers; Heiko C. Bergmann; Marcel G. M. Olde Rikkert; Roy P. C. Kessels (Journal of Aging Research)
Emotional content typically facilitates subsequent memory, known as the emotional enhancement effect. We investigated whether emotional content facilitates spatial and item memory in patients with Alzheimer's dementia (AD). Twenty-three AD patients, twenty-three healthy elderly, and twenty-three young adults performed a picture relocation task and a delayed recognition task with positive, negative, and neutral stimuli. AD patients showed a benefit in immediate spatial memory for positive pictures, while healthy young and older participants did not benefit from emotional content. No emotional enhancement effects on delayed item recognition were seen. We conclude that AD patients may have a memory bias for positive information in spatial memory. Discrepancies between our findings and earlier studies are discussed.